2020
DOI: 10.1111/hel.12728
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between Helicobacter pylori infection and childhood overweight/obesity

Abstract: Background The reduction in the prevalence of Helicobacter pylori (H. pylori) infection in developed countries coincides with the increasing incidence of obesity and might be a contributing factor to the obesity epidemic. We aimed to evaluate the association between H. pylori infection and childhood overweight/ obesity in Israeli children. Material and Methods Patients diagnosed with H. pylori infection by endoscopy, histology, and a positive culture, between January 2013 and August 2018, were identified and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…H. pylori has been investigated in relation to pediatric obesity, with two studies showing lower H. pylori seropositivity in children and adolescents with obesity (22,23). Other studies found no association (24,25). One European study demonstrated an increase in body mass index (BMI) after eradication of H. pylori (26), similar to an earlier finding in adults (27).…”
Section: Introductionmentioning
confidence: 70%
“…H. pylori has been investigated in relation to pediatric obesity, with two studies showing lower H. pylori seropositivity in children and adolescents with obesity (22,23). Other studies found no association (24,25). One European study demonstrated an increase in body mass index (BMI) after eradication of H. pylori (26), similar to an earlier finding in adults (27).…”
Section: Introductionmentioning
confidence: 70%
“…Numerous studies have found an association between H. pylori infection and obesity [ 55 ], but some studies have not found an association between H. pylori infection and childhood obesity or overweight [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a study conducted in Taiwan involving 176 children aged 10–19 years old found a higher prevalence of H. pylori seropositivity among obese children compared to non‐obese children (18.2% vs. 40%) 23 . However, two other studies focusing on obese children undergoing bariatric surgery in Korea and Israel respectively failed to replicate these findings, providing support for the absence of an association 24 . Furthermore, the impact of H. pylori eradication on BMI was examined in various studies.…”
Section: Clinical Evidence Of the Involvement Of Helicobacter Pylori ...mentioning
confidence: 99%
“…23 However, two other studies focusing on obese children undergoing bariatric surgery in Korea and Israel respectively failed to replicate these findings, providing support for the absence of an association. 24 Furthermore, the impact of H. pylori eradication on BMI was examined in various studies. In a retrospective multicenter cohort study from Korea, employing the Propensity Score-matched method, it was found that H. pylori eradication did not result in significant changes in BMIs.…”
Section: Obesitymentioning
confidence: 99%